MARKETING STRATEGY OF COMMERCIAL HEALTH INSURANCE COMPANY - Cut Zaraswati; Ujang Sumarwan; Hari Wijayanto (Indonesian Journal of Business and Entrepreneurship (IJBE), 2017)
The objectives of this research are to: 1) compare the effect of premium earnings products of health insurances after the launching of national social health insurance (JKN)-BPJS (Badan Penyelenggara Jaminan Sosial) for health; 2) analyze the internal and external factors of private/commercial health insurance companies; 3) formulate a marketing strategyy for health insurance product after the operation of JKN-BPJS for health.  It is a challenge for commercial health insurance to survive and thrive with the existence of JKN-BPJS for health which is compulsory to Indonesia’s citizens to be a member. The research begins by analyzing premium earnings of the commercial health insurance company one year before and after the implementation of JKN-BPJS for health, the intensive interviews and questionnaires to the chosen resource person (purposive samplings), the analysis on Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), Matrix IE and SWOT are used in the research. Then it is continued by arranging a strategic priority using Analytical Hierarchy Process (AHP).  The result from the research is there is totally no decreasing premium earnings for the commercial health insurance company although the growth trend shows a slight drop.  The appropriate strategy for the health insurance company in the commercial sector is the differentiation where the implication is involving customer service quality improvement, product innovation, and technology and infrastructure development.      Keywords:  commercial health insurance company, Marketing Strategy, AHP Analysis, national social health insurance